Characterization of Bacillus cereus Group Isolates From Human Bacteremia by Whole-Genome Sequencing - Bianco, Angelica; Capozzi, Loredana; Monno, Maria Rosa; Del Sambro, Laura; Manzulli, Viviana; Pesole, Graziano; Loconsole, Daniela; Parisi, Antonio (Frontiers in Microbiology, 2021)
Members of the Bacillus cereus group are spore-forming organisms commonly associated with food poisoning and intestinal infections. Moreover, some strains of the group (i.e. Bacillus cereus sensu stricto and B. thuringiensis) can cause bacteremia in humans, mainly in immunocompromised individuals. Here we performed the genetic characterization of seventeen human clinical strains belonging to B. cereus group isolated from blood culture. The whole genome sequencing (WGS) revealed that the isolates were closely related to B. cereus sensu stricto and B. thuringiensis type strain. Multilocus sequence typing analysis performed on the draft genome revealed the genetic diversity of our isolates, which were assigned to different sequence types. Based on panC nucleotide sequence, the isolates were grouped in the III and IV phylogenetic group. The NHE, cer and inhA gene cluster, entA, entFM, plcA and plcB were the most commonly detected virulence genes. Even if, we did not assess the ability to generate biofilm by phenotypic tests, we verified the prevalence of biofilm associated genes using an in silico approach. A high prevalence of pur gene cluster, xerC, clpY, codY, tasA, sipW, sinI and sigB genes was found. Genes related to the resistance to penicillin, trimethoprim and ceftriaxone were identified in most of the isolates. Intriguingly, the majority of these virulence and AMR genes appeared to be evenly distributed among B. cereus s.s. isolates as well as closely related to B. thuringiensis isolates. We showed as the WGS represents a good approach to rapidly characterize B. cereus group strains, being able to give useful information about genetic epidemiology, the presence of virulence and antimicrobial genes, and finally about the potential hazard related to this underestimated risk.